2017
DOI: 10.4328/jcam.4801
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Postpartum Depression and Intimate Partner Violence

Abstract: ÖzetAmaç: Eş tarafından kadına yönelik şiddetin depresyonu tetiklediği bildirilmektedir. Bu çalışmada postpartum dönemde depresyon geçiren ve geçir-meyen kadınlardaki eş şiddetine maruziyetin postpartum depresyona etkisinin araştırılması amaçlandı. Gereç ve Yöntem: Aile hekimliğince gebelik takibi yapılan ve doğum sonrası izlemi yapılan postpartum döneminin 4. haftasın-da olan kayıtlı 128 kadın olgu çalışmaya dahil edildi. Daha önce ruhsal hastalık öyküsü ve ilaç kullanımı olmayan postpartum dönemindeki kadınl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Over half of the studies (n = 18) in this scoping review collected data from samples within the United States [2][3][4][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Three articles came from Turkey [32][33][34], two came from South Africa [35,36] and one article came from Germany [37], Ghana [38], Hong Kong [39], India [40], Malaysia [41], and Palestine [42]. A single article used data collected as part of a multi-country study of China, Cambodia, Papua New Guinea, and Sri Lanka [43].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Over half of the studies (n = 18) in this scoping review collected data from samples within the United States [2][3][4][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Three articles came from Turkey [32][33][34], two came from South Africa [35,36] and one article came from Germany [37], Ghana [38], Hong Kong [39], India [40], Malaysia [41], and Palestine [42]. A single article used data collected as part of a multi-country study of China, Cambodia, Papua New Guinea, and Sri Lanka [43].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All but two studies [39,41] had entirely female samples. The race/ethnicity of the sample was not documented in 12 studies [30,[32][33][34][36][37][38][39][40][41][42][43]. Six of the studies reported having a sample in which 50% or more identi ed as white [3,4,18,28,29,31].…”
Section: Samplementioning
confidence: 99%
See 3 more Smart Citations